2022
DOI: 10.1097/gco.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

BMI and miscarriage after IVF

Abstract: Purpose of reviewTo summarize recent findings related to the risk of miscarriage in women with elevated BMI undergoing IVF, and the mechanisms involved in said risk.Recent findingsMiscarriage rates are increased in overweight and obese women in both natural and assisted reproduction. Oocyte and embryo quality assessed according to classic morphological static parameters does not seem to be affected by excessive female body weight. Despite the initial lack of consensus between studies regarding embryo morphokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…15,16 Literature suggests that whether they used assisted reproductive techniques or natural conception, overweight or obese women are at a considerably higher risk of miscarriage. [17][18][19][20][21] CRL is a significant indicator of early fetal growth and neonatal outcome. Thelatest study has reported various maternal characteristics such as maternal age, parity, BMI, and folic acid supplementation as independently associated factors of CRL in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Literature suggests that whether they used assisted reproductive techniques or natural conception, overweight or obese women are at a considerably higher risk of miscarriage. [17][18][19][20][21] CRL is a significant indicator of early fetal growth and neonatal outcome. Thelatest study has reported various maternal characteristics such as maternal age, parity, BMI, and folic acid supplementation as independently associated factors of CRL in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…In both natural and ART, MR is risen in overweight and obese women [6]. The performance of oocytes and embryos as measured by classic morphometric static variables does not appear to be influenced by inordinate female body weight.…”
Section: Obesity Has a Negative Impact On Ivf Outcomes Bmi And Miscar...mentioning
confidence: 93%
“…women have the same embryo morphokinetic progression, blastocyst forming incidence, and blastocyst morphological characteristics [6]. On the contrary side, García-Ferreyra et al revealed that a higher BMI impacts cell growth and decreases childbirth, implantation rate, and LBR [7].…”
Section: Bellver Et Al Stated That Obese and Normal-weightmentioning
confidence: 99%
“…Among this vast population, 40% of women at reproductive age are prone to infertility or subfertility 2 . Although in vitro fertilization (IVF) is an effective treatment for infertility, OW is associated with an increased rate of fetal loss or miscarriage 3–5 . It has been suggested that OW has a detrimental effect on ovarian responsiveness and oocyte quality, 6 however, more evidence is needed to elucidate the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although in vitro fertilization (IVF) is an effective treatment for infertility, OW is associated with an increased rate of fetal loss or miscarriage. [3][4][5] It has been suggested that OW has a detrimental effect on ovarian responsiveness and oocyte quality, 6 however, more evidence is needed to elucidate the mechanism. Accumulating evidence indicates that granulosa cells (GCs), which play fundamental roles in follicular development, are susceptive to the altered follicular microenvironment in OW women.…”
Section: Introductionmentioning
confidence: 99%